Implementation of green infrastructure for rehabilitation of degraded lands in urban areas of Bali: Challenges and roles of universities - Dwijendra, Ngakan Ketut Acwin; Winastri K, Desak Ayu Krystina; Krishna K, Dewa Ngakan Made Bagus (Journal of Degraded and Mining Lands Management, 2025)
Urban areas in Bali are facing increased risks due to the effects of climate change and intensive land degradation, resulting from rapid land conversion and non-environmentally friendly development processes. Green infrastructure provides an integrated and environmentally friendly solution for rehabilitating degraded lands and enhancing the resilience of cities. This research examines the application of green infrastructure in four urban locations in Bali—Denpasar, Badung, Gianyar, and Tabanan—emphasizing the rehabilitation of ecosystems and the role of universities as a central hub. Based on a qualitative case study approach corroborated by quantitative environmental data, the study evaluated the efficacy of green infrastructure projects in improving water and soil quality, minimizing erosion, and improving infiltration rates. Results indicated substantial ecological benefits with implementation, highlighting the role of institutions of higher learning in research, public education, and technological innovation. Although the findings are encouraging, numerous challenges remain, including inadequate financial support, sporadic project allocation, and limited public awareness. This study provided policy and practical recommendations for integrating green infrastructure into spatial planning and enhancing university-government collaboration to ensure sustainable urban development and land reclamation in climate-vulnerable regions.